Vektorių kvantavimo metodų ir daugiamačių skalių junginys daugiamačiams duomenims vizualizuoti - Molytė, Alma; Kurasova, Olga (Information & Media, 2009)
Darbe pateikiama lyginamoji dviejų vektorių kvantavimo metodų (saviorganizuojančių neuroninių tinklų ir neuroninių dujų) analizė. Neuronai nugalėtojai, kurie gaunami vektorių kvantavimo metodais, yra vizualizuojami daugiamačių skalių metodu. Tirta kvantavimo paklaidos priklausomybė nuo vektorių nugalėtojų skaičiaus. Išsiaiškinta, kuris vektorių kvantavimo metodas yra tinkamesnis jungti su daugiamačių skalių metodu, t. y. vizualizavus neuronus nugalėtojus „atskleidžiama“ analizuojamųduomenų struktūra.Combination of Vector Quantization and Multidimensional ScalingAlma Molytė, Olga KurasovaSummaryIn this paper, we present a comparative analysis of a combination of two vector quantization methods (self-organizing map (SOM) and neural gas (NG)), based on neural networks and multidimensional scaling that is used for visualization of codebook vectors obtained by vector quantization methods. The dependence of neuron-winners, quantization and mapping qualities, and preserving of a data structure in the mapping image are investigated. It is established that the quantization errors of NG are smaller than that of the SOM when the number of neurons-winners is approximately equal. It means that the neural gas is more suitable for vector quantization. The data structure is visible in the mapping image even when the number r of neurons-winners of NG is small enough. If the number r of neurons-winners of the SOM is larger, the data structure is visible, as well.8px;">